Rock-Joint Micromechanics: Relationship of Roughness to Closure and Wave Propagation - Misra, Anil S.; Marangos, Orestes (My University, 2011)
The closure behavior of rock joints is intimately related to joint roughness. Here we utilize a micromechanical approach that explicitly considers asperity interactions on joint surfaces to study the rock-joint closure and wave propagation behavior. Elastic deformations and inelastic frictional sliding are considered at inclined asperity contacts. Rock-joint roughness is modeled through distributions of asperity heights and asperity contact orientations. The micromechanical approach developed in this paper establishes the link between the rock-joint closure behavior, the initial overlap of the joints, the asperity height distribution parameters, and the average asperity slope. The model is verified by comparison with experimental measurements. Subsequently a parametric study is performed. The results show that rock joints with the same roughness can exhibit a range of closure behavior depending upon initial overlap and rock intrinsic friction. Therefore, unique descriptions of rock-joint closure behavior are elusive. Finally, the model-predicted nonlinear normal and shear stiffness are used to investigate the reflection and transmission of plane waves at rock joints.
Keywords: Asperity; Contact; Force displacement; Micromechanics; Rock joint; Wave propagation